MOTIVASI VIETNAM MENJALIN KERJASAMA DENGAN INDONESIA DALAM BIDANG PERTAHANAN TAHUN 2010-2017 - Widyatama, Alferro; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to explain how defense cooperation is established between Indonesia and Vietnam in 2010-2017. The security of territorial sovereignty is one of the national interests which is always pursued by the state. Every country in the world needs a safe condition to live a state life and to obtain it then the defense system will always be needed. To meet these needs, Vietnam is trying to strengthen its defense by buying weapons from other countries, one of them from Indonesia. Indonesia is known as the best weapon system's main tool manufacturer in Southeast Asia, as evidenced by the existence of three SOEs namely PT. DI, PT. PINDAD, and PT. PAL. The Memorandum of Understanding on Enhancing Cooperation between Defense Officers and Related Defense Related Activities agreed in 2010 and good relationships that have been established for approximately 50 years is another factor in Vietnam making Indonesia a partner in defense cooperation.This research data is obtained from books, journals, official documents, and websites that support the hypothesis. The author uses the neorealism approach of Kenneth Waltz and the nation-state analysis. And the theory used in this research is the theory of decision making and national interest.The result of the research shows that the relationship between Vietnam and Indonesia so far has been running well, marked by the holding of working visit and honorary visit by both countries, and the exchange of delegation and joint training which is the scope of cooperation contained in the Memorandum of Understanding Cooperation between Indonesia-Vietnam Defense Officials and Related Defense Related Activities signed in 2010. It is expected that the cooperation between the two countries will be better in the future, considering the many threats that will be faced in accordance with the times, not only from within but also from outside the region.Keywords: Defense Cooperation, Regional Sovereignty, National Interest.